Recruitment of Cytosolic J-Proteins by TOM Receptors Promotes Mitochondrial Protein Biogenesis - Opaliński, Łukasz (Cell Rep, 2018)
Mitochondria possess elaborate machineries for the import of proteins from the cytosol. Cytosolic factors like Hsp70 chaperones and their co-chaperones, the J-proteins, guide proteins to the mitochondrial surface. The translocase of the mitochondrial outer membrane (TOM) forms the entry gate for preproteins. How the proteins are delivered to mitochondrial preprotein receptors is poorly understood. We identify the cytosolic J-protein Xdj1 as a specific interaction partner of the central receptor Tom22. Tom22 recruits Xdj1 to the mitochondrial surface to promote import of preproteins and assembly of the TOM complex. Additionally, we find that the receptor Tom70 binds a different cytosolic J-protein, Djp1. Our findings suggest that cytosolic J-proteins target distinct TOM receptors and promote the biogenesis of mitochondrial proteins.